Influence of the plasma-immersion ion implantation of titanium on the structure, morphology, and composition of the surface layer of Zr–1Nb alloy; Journal of Surface Investigation. X-ray, Synchrotron and Neutron Techniques; Vol. 11, iss. 2 - Sutygina A. N. Alina Nikolaevna; Nikitenkov N. N. Nikolai Nikolaevich; Kashkarov E. B. Egor Borisovich; Syrtanov M. S. Maksim Sergeevich; Lukash V. Voleski; Louda P. Petr; Pryamushko T. S. Tatiana Sergeevna; Sypchenko V. S. Vladimir Sergeevich; Khashkhash A. M. Adel Mokhammed ali (2017, 2017)
Title screen